(untitled) (Al-Qamar, 2023)
The twentieth century A.D was a very important period for Muslims in Pakistan and India. In the Western world, that universal revolution had reached its culmination, as a result of which modern man, instead of Allah himself, reorganized the whole world of thought and action based on inductive science. The tenets of religion that seemed to contradict the new conception of life were abandoned, and with this state of mind, the Western nations gained political supremacy over the Eastern countries. Doubt, atheism and secularism began to take shape here as well. This was due to the attacks on Islam by Western Christianity and Western-nurtured Orientalism. These attacks on Western thought and Christianity were taking place under the auspices of the imperialist powers. At the same time, these nations were teaching civilization to the eastern nations. Muslim subcontinent was undergoing a process of political and cultural influence. In the field of knowledge, these things affected his intellectual perseverance and resilience in the field of knowledge. A trend of liberalism and reconciliation emerged in the religious literature of the time, represented by Sir Syed Ahmad Khan. After the establishment of Pakistan, some people with the same mindset came forward who expressed their commitment and deep connection with the Qur’ān, He wrote many books and published journals to popularize Qur’ānic teachings. He taught Qur’ānic discourses and wrote commentaries, but through the maneuvering, and misinterpretation of the Qur’ānic verses, he developed the structure of an Islam whose features were radically different from the real Islam.